Effects of Kaduna Refining and Petrochemical Corporation Effluents on the Abundance and Distribution of Phytoplankton Community along River Rido, Kaduna, Nigeria (Journal of Environmental Bioremediation and Toxicology, 2021)
The effects of effluent discharged from Kaduna Refining and Petrochemical Corporations (KRPC) on the Phytoplankton species distribution and abundance was studied along river Rido for a period of twelve months from February 2013 to January 2014. A total of Ninety-three (93) species of phytoplankton distributed in five divisions were recorded from four different study stations (A, B, C and D) along the river. Random sequential sampling was employed for selecting a sampling station. Physicochemical parameters were determined in accordance with the standard procedure for wastewater assessment guidelines of American Public Health Association (APHA). Phytoplankton identification was done using appropriate reference materials. The phytoplankton community was dominated by Bacillariophyta9 constituting 78.98% with 41 species, followed by Chlorophyta (6.67%) having 25 species, and then Cyanophyta (6.46%) having 12 species, while 10 species of Dinophyta and 5 species of Euglenophyta constituting 5.42% and 2.49% respectively were observed. The results from the study revealed low density of phytoplankton in station B, while high density of phytoplankton was observed in stations A and D. The physicochemical parameters showed both seasonal and spatial variations. Values of some parameters studied were observed to be above Federal Environmental Protection Agency (FEPA) limits at station B. Thus, effluent from KRPC is a source of contamination of water quality and adversely affects phytoplankton community along river Rido. Therefore, effluent retention facility should be established for long term treatment of effluent before discharge into the river
Keywords: Effluent; Petroleum wastewater; Phytoplankton; Physicochemical; Rido